The Case of the Disappearing/Appearing Slow Learner: An Interpretive Mystery - W. John Williamson (University of Calgary, 2014)
This interpretive essay attempts to demonstrate the potential good that might come from approaching a hermeneutic phenomenological study as a hard-boiled detective story in the tradition of Raymond Chandler. The authors attempt to explain the hermeneutic warrants for such an adventureâ€”that is, for how and why a topic like the categorization and treatment of students in the public education system as â€œslow learnersâ€ might be approached as a detective story. The parallels between detective fiction, Chandlerâ€™s work as a noir novelist, and hermeneutics are drawn out. Attention is drawn to the ground of our interpretive relationship with the world in Heideggerâ€™s notion of the â€œas structureâ€ of interpretation. A case is made for seeing the hard-boiled detective story as a hermeneutic venue for shaking up commonsense understandings of how we have come to see and do education with those students designated as slow in their learning.